Audiences for Science Communication in the United States. Issue 8 (17th November 2018) - Besley, John C.
ABSTRACT: The US National Science Foundation collects biennial data on views about science and technology (S&T). Analyses have typically focused on the degree to which demographics, knowledge, and attitudes predict S&T support or views about specific technologies or issues. Published efforts do not appear to have focused on identifying latent classes within the data. Initial analyses using latent profile analysis suggests that Americans can be categorized into six substantive audience groups when it comes to views about S&T. These groups vary by demographics, including scientific background and ideology, as well as in views about S&T. Post hoc analyses explore how "class-focused" analyses may provide additional insight beyond what can be obtained from "variable-focused" analyses.